Dampak Perubahan Iklim dan Cuaca Ekstrem terhadap Dinamika Penularan Demam Berdarah Dengue: Sebuah Tinjauan Literatur - Mulyani; Manda (Awatara Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern, particularly in tropical and subtropical regions. Climate change and the increasing frequency of extreme weather events, such as flooding and irregular rainfall patterns, play a significant role in influencing dengue transmission dynamics through their effects on mosquito vectors and viral replication. This article aims to narratively review scientific evidence on the relationship between climate change, extreme weather, and dengue transmission. A narrative literature review was conducted using relevant national and international publications retrieved from databases including PubMed, Scopus, Google Scholar, and ScienceDirect, covering the period from 2015 to 2024. The reviewed studies examined the influence of key climatic variables—temperature, rainfall, and humidity—as well as extreme weather events such as flooding on dengue incidence. The findings indicate that increased temperature, variable rainfall, and high humidity are consistently associated with a higher risk of dengue transmission. Flood events were also found to contribute to increased mosquito breeding sites and subsequent rises in dengue cases following flooding periods. These findings highlight the role of climate change in exacerbating dengue risk and emphasize the need for adaptive disease control strategies. Integrating climate information into dengue surveillance and public health policy is essential to strengthen dengue prevention and control in the context of ongoing climate change.